2016
DOI: 10.1002/icd.1957
|View full text |Cite
|
Sign up to set email alerts
|

Social Competence at the Playground: Preschoolers During Recess

Abstract: of outdoor physical play for preschoolers' social success. Moreover, the study suggests that the environment in which children play has an important effect on the adaptive nature of their play.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 46 publications
(69 reference statements)
2
42
0
1
Order By: Relevance
“…According to this, it was found that as children's play skills increase, their social competences increase, whereas their levels of angeraggression and anxiety-withdrawal decrease. When literature is examined, it is seen that many studies have found that social play and social competence are empirically related (e.g., Fantuzzo, Sekino, & Cohen, 2004;Gagnon & Nagle, 2004;Gülay Ögelman & Erten Sarıkaya, 2014;Howes & Matheson, 1992;Veiga et al, 2017). It is seen that such interactive play is parallel to children's social development and that this play has a powerful influence on future social competence and interpersonal relationships (Johnson, Ironsmith, Snow, & Poteat, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to this, it was found that as children's play skills increase, their social competences increase, whereas their levels of angeraggression and anxiety-withdrawal decrease. When literature is examined, it is seen that many studies have found that social play and social competence are empirically related (e.g., Fantuzzo, Sekino, & Cohen, 2004;Gagnon & Nagle, 2004;Gülay Ögelman & Erten Sarıkaya, 2014;Howes & Matheson, 1992;Veiga et al, 2017). It is seen that such interactive play is parallel to children's social development and that this play has a powerful influence on future social competence and interpersonal relationships (Johnson, Ironsmith, Snow, & Poteat, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This is so because play supports peer interaction which predicts the children's social skills and peer relations, cooperation and positive emotions (Mize & Pettit, 1997). Social competence is promoted by the quality of peer interaction within play (Newton & Jenvey, 2011;Veiga et al, 2017). In other words, children who are able to maintain peer relations and who have a closer social interaction while playing are socially more competent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is an emerging literature concerning the use of such technologies to study individual differences in childhood social behaviour. Veiga and colleagues have used RFID to establish that frequent proximity to other children during play is a good predictor of social competence [9]. In the present study we were motivated include movement data into the study of play as another source of social insights.…”
Section: Introductionmentioning
confidence: 99%